Impact of immigration in presentation and outcomes of hepatocellular carcinoma in the USA. Issue 1 (January 2019) - Ashhab, Ashraf A.; Rodin, Holly; Powell, Jesse; Debes, Jose D.
Abstract : Background and aims: Hepatocellular carcinoma's (HCC) epidemiology and prognosis differs among regions across the globe, largely because of environmental factors and underlying liver disease. Little is known about the changes led by immigration and the effect on HCC outcome. We aimed to understand the effect of immigration on HCC. Patients and methods: A retrospective cohort study of patients diagnosed with HCC was carried out in a tertiary center in the USA between 2005 and 2016. We characterized individuals as US born or having immigrated there after being born elsewhere. Variables related to clinical presentation, surveillance, therapy, and survival were evaluated. Results: A total of 232 HCC cases were included, 169 US born (73%) and 63 immigrants (27%). Both groups were diagnosed with HCC at similar ages (60 vs. 62 years, P =0.13). Hepatitis C was the most common underlying liver disease in the US-born population compared with the immigrant population (83 vs. 52%, P <0.001), whereas hepatitis B was more common in the latter (4 vs. 29%, P <0.001). Interestingly, hepatitis B virus-related HCC was diagnosed at similar ages in US-born and immigrant individuals (59 and 57 years). At the time of diagnosis, both populations had similar tumor sizes, rates of metastasis, and diagnosis during surveillance. One-year survival was similar in both groups (65 vs. 63%). Conclusion: Immigrants that develop HCC have different underlying liver disease than those born in the USA, but similar HCC characteristics and outcomes, even when including hepatitis B virus-related HCCs. Our study, albeit small, suggests that changes in the environment by immigration leads to clinical adaptation of HCC.